2002
DOI: 10.1142/s0217751x02010534
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological Evolution in a Type-0 String Theory

Abstract: We study the cosmological evolution of a type-0 string theory by employing noncriticality, which may be induced by fluctuations of the D3 brane worlds. We check the consistency of the approach to O(α ′ ) in the corresponding σ-model. The ten-dimensional theory is reduced to an effective four-dimensional model, with only time dependent fields.We show that the four-dimensional universe has an inflationary phase and graceful exit from it, while the other extra dimensions are stabilized to a constant value, with t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(101 citation statements)
references
References 28 publications
3
98
0
Order By: Relevance
“…This important and by far not complete issue is highly model dependent, and it relies on specific properties of the underlying microscopic string theory, involving detailed scenaria of compactification, moduli field stabilization etc. In the literatute there are toy brane-inspired, non-critical-string cosmological models, where such approximately constant dilatons during early epochs of the Universe could be realised explicitly [13,14,25]. We also remark that similar assumptions are made in generic dilaton quintessence scenaria of critical strings [27].…”
Section: Modified Boltzmann Equation In Non-critical Stringsmentioning
confidence: 76%
See 3 more Smart Citations
“…This important and by far not complete issue is highly model dependent, and it relies on specific properties of the underlying microscopic string theory, involving detailed scenaria of compactification, moduli field stabilization etc. In the literatute there are toy brane-inspired, non-critical-string cosmological models, where such approximately constant dilatons during early epochs of the Universe could be realised explicitly [13,14,25]. We also remark that similar assumptions are made in generic dilaton quintessence scenaria of critical strings [27].…”
Section: Modified Boltzmann Equation In Non-critical Stringsmentioning
confidence: 76%
“…through an appropriate minimisation of its potential, being thus stabilised at early times. In such on-shell situations, as opposed to our non-equilibrium (off-shell) model studied in this and in previous articles [1,25,26], matter particles may…”
Section: Modified Boltzmann Equation In Non-critical Stringsmentioning
confidence: 88%
See 2 more Smart Citations
“…Reducing them to four-dimensions and assuming that all the fields are time dependent we get an effective four-dimensional theory. We found that this theory in a Robertson-Walker background has an inflationary phase but we cannot exit from this phase in a smooth way [17]. We believe that the central issue of inflationary cosmology is not how we can get an inflationary phase, but how we can exit from it.…”
Section: Discussionmentioning
confidence: 84%